Whole Genome Sequence Analysis of CTX-M-15 Producing Klebsiella Isolates Allowed Dissecting a Polyclonal Outbreak Scenario - Becker, Laura; Fuchs, Stephan; Pfeifer, Yvonne; Semmler, Torsten; Eckmanns, Tim; Korr, Gerit; Sissolak, Dagmar; Friedrichs, Michael; Zill, Edith; Tung, Mei-Lin; Dohle, Christian; Kaase, Martin; et al. (Frontiers in Microbiology, 2018)
Extended-spectrum β-lactamase (ESBL) producing Klebsiella pneumoniae pose an important threat of infection with increased morbidity and mortality, especially for immunocompromised patients. Here we use the rise of multi-drug resistant K. pneumoniae in a German neurorehabilitation centre from April 2015 to April 2016 to dissect the benefit of whole genome sequencing (WGS) for outbreak analyses. In total, 53 isolates were obtained from 52 patients and examined using WGS. Two independent analysis strategies (reference-based and -free) revealed the same distinct clusters of two CTX-M-15 producing K. pneumoniae clones (ST15, n=31; ST405, n=7) and one CTX-M-15 producing K. quasipneumoniae strain (ST414, n=8). Additionally, we determined sequence variations associated with antimicrobial resistance phenotypes in single isolates expressing carbapenem and colistin resistance, respectively. For rapid detection of the major K. pneumoniae outbreak clone (ST15), a selective triplex PCR was deduced from WGS data of the major outbreak strain and K. pneumoniae genome data deposited in central databases. Moreover, we introduce two novel open-source applications supporting reference genome selection (refRank; https://gitlab.com/s.fuchs/refRank) and alignment-based SNP-filtering (SNPfilter; https://gitlab.com/s.fuchs/snpfilter) in NGS analyses.